ASSESSING THE EFFECTIVENESS OF A NURSE-LED PATIENT EDUCATION PROGRAM ON MEDICATION ADHERENCE AND GLYCEMIC CONTROL AMONG TYPE 2 DIABETES PATIENTS IN SAUDI ARABIA: A CROSS-SECTIONAL STUDY - Mohammed Mutlaq Almutairi, Khalid Khalaf Subayyil Alharbi, Bader Duwal Alrahef Alruwaili, Fayez Badea Sasaa Alruwaili, Ibrahim Munis Alanazi, Abdullah Fuhaid Al-Anazi, Abdullah Saeed N Alobaiwi (Chelonian Research Foundation, 2022)
Diabetes is a chronic condition that requires ongoing management, and patient education is a crucial component of diabetes care. This cross-sectional study aims to assess the effectiveness of a nurse-led patient education program on medication adherence and glycemic control among type 2 diabetes patients in Saudi Arabia. A total of 500 type 2 diabetes patients were recruited from diabetes clinics in Riyadh, Saudi Arabia. Participants were divided into two groups: those who attended a nurse-led patient education program and those who received standard care. Data were collected using a structured questionnaire and medical records. The primary outcomes were medication adherence, measured using the Morisky Medication Adherence Scale (MMAS-8), and glycemic control, assessed by glycated hemoglobin (HbA1c) levels. The data were analyzed using descriptive statistics, chi-square tests, and multiple linear regression. The results showed that patients who attended the nurse-led education program had significantly higher medication adherence scores and better glycemic control compared to those who received standard care. The findings highlight the importance of patient education in diabetes management and the potential of nurse-led programs to improve patient outcomes in Saudi Arabia. Keywords: diabetes, patient education, medication adherence, glycemic control, nurse-led program, Saudi Arabia